2011
DOI: 10.1007/bf03325321
|View full text |Cite
|
Sign up to set email alerts
|

Social appearance anxiety and bulimia nervosa

Abstract: Social appearance anxiety is an unexplored concept in eating disorders (ED). It refers to social anxiety surrounding overall appearance, including body shape, and fear of negative evaluation by others. It is potentially relevant to those with bulimia nervosa (BN) as both social anxiety and body image disturbance are commonly experienced by patients. Thirty women with BN and forty healthy controls (HC) completed the Social Appearance Anxiety Scale (SAAS), a 16-item self-report questionnaire. ED cognitions and b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
29
2
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 20 publications
6
29
2
2
Order By: Relevance
“…As in the current study, when the raw scores on the SAAS of the participants are compared, other studies have found [29,30] that ED patients obtained a higher score than control community groups. Although, to our knowledge, no research has analysed the role of gender and age in the specific fear of judgment based on appearance (SAA) in adult or adolescent samples, the gender and age differences across adolescents found in this research converged with a large body of research indicating that in general terms body and overall appearance concerns, social fears and particularly negative evaluation fears, and social anxiety are more salient from mid-adolescence onwards and across female participants [26,27,32,34,37,47,62,69].…”
Section: Discussionsupporting
confidence: 53%
See 3 more Smart Citations
“…As in the current study, when the raw scores on the SAAS of the participants are compared, other studies have found [29,30] that ED patients obtained a higher score than control community groups. Although, to our knowledge, no research has analysed the role of gender and age in the specific fear of judgment based on appearance (SAA) in adult or adolescent samples, the gender and age differences across adolescents found in this research converged with a large body of research indicating that in general terms body and overall appearance concerns, social fears and particularly negative evaluation fears, and social anxiety are more salient from mid-adolescence onwards and across female participants [26,27,32,34,37,47,62,69].…”
Section: Discussionsupporting
confidence: 53%
“…Employing a female adult sample of 60 outpatients with EDs, Claes et al [10] supported the one-factor model of the SAAS and found that its score was significantly positive in relation to mistrust of others, social detachment, emotional lability and desire to become thinner. Evidence that ED patients obtained higher SAAS scores than matched healthy controls exists as well [29,30].…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…Neural mechanisms underlying the known association between social-appearance anxiety, a potential NVS construct, and BN symptoms (Koskina et al 2011, Levinson et al 2013) are examined when women imagine that someone is comparing their own bodies to other women’s (Spangler and Allen 2012). Women with BN demonstrate greater activity in the rostral-ventral anterior cingulate cortex than healthy controls upon exposure to obese (vs. thin) bodies (Spangler and Allen 2012).…”
Section: Neural Circuitsmentioning
confidence: 99%